Nutrient concentration in sediments accumulated in pre-treatment basins of urban LID technologies - Geronimo, Franz Kevin F. (Animo Repository, 2019)
In this study, the contribution of pre-treatment basins of low impact development (LID) technologies to nutrient reduction performance was evaluated by understanding the distribution of nutrient in sediments accumulated in each system. The captured sediments were mostly silt to medium sand ranging from 9% to 92% of the sediments collected. Greater average N and P concentrations were found in silt particles amounting to 345 mg/kg and 696 mg/kg, respectively compared to sand and gravel. Although, N concentrations in accumulated sediments were found to be highly variable at different particle sizes (CV: 0.24 to 0.77) compared to P concentration (CV: 0.08 to 0.36) attributed to effective P treatment mechanism through deposition compared to complex nitrogen removal mechanisms. In addition, the difference between N and P concentrations of sediments collected in the pre-treatment basins of LID technologies and in-situ soil was attributed to the continuous pollutant input to the LID technologies during storm events. The study proved that pre-treatment basins of stormwater LID technologies reinforced the nutrient removal performances through sediment retention. The findings of this research may be used to design pre-treatment basins of LID technologies considering nutrients as a limiting factor. © IWA Publishing 2019 Water Science & Technology